Composite membrane structure for thermophoresis optical tweezers capture and preparation method and application thereof

By using composite film structures, including chromium film and silica film in thermal optical tweezers, the problem of insufficient thermal field strength in the prior art is solved, and efficient sample capture and manipulation at different wavelengths is achieved, ensuring capture stability and accuracy.

CN119170318AInactive Publication Date: 2024-12-20SHENZHEN UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411660243.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2024-12-20
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The current thermal optical tweezers have a decrease in absorption when the wavelength is greater than 500nm, resulting in insufficient thermal field strength and making it difficult to achieve high-precision control of a large range and multiple targets.

Method used

The composite film structure is adopted, including the substrate, chromium film layer and silica film layer. The thickness of the chromium film layer is 10nm-15nm and the thickness of the silica film layer is 25nm-30nm. It is prepared by evaporation and radio frequency magnetron sputtering. The high absorption rate and slow thermal diffusion properties of the chromium film form a strong thermal gradient field, and a silica film is plated on the surface of the chromium film to isolate the sample.

Benefits of technology

A larger and more stable thermal gradient field is formed at different laser wavelengths, achieving efficient thermal strobe capture and manipulation of the sample, avoiding the impact of chromium film toxicity on the sample, and improving the accuracy and stability of the capture.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119170318A_ABST
    Figure CN119170318A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of optical tweezers, and discloses a composite film structure for capture of thermophoresis optical tweezers and a preparation method and application thereof, and the composite film structure for capture of thermophoresis optical tweezers sequentially comprises a substrate, a chromium film layer and a silicon dioxide film layer from bottom to top. A local non-uniform temperature field is generated by irradiating the composite film structure through laser, and thermophoresis capture of particles is realized by utilizing a thermal gradient field near a hot spot; when a chromium-silicon dioxide substrate is used for photo-thermal capture, a spatial light modulator is used for generating an array light trap (such as 100 or more), on-chip capture of particles can be carried out at the array photo-thermal trap, the capture power of each point is smaller than 0.1 mW, and under the condition that the laser power is the same, on-chip capture of particles can be carried out. And a larger and more stable thermal gradient field can be generated compared with substrate materials such as gold, graphene and the like so as to assist more types of photo-thermal capture.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of optical tweezers, and in particular to a composite membrane structure for capturing by thermophoresis optical tweezers, and a preparation method and application thereof. Background Art

[0002] Optical tweezers is a classic manipulation technology for micro-nano-sized particles or cells. It focuses the light field to form a three-dimensional potential well to directly capture tiny particles. During the capture process of optical tweezers, the material absorbs light energy and produces a photothermal effect, forming a non-uniform temperature field at the laser focus. If it is not controlled, it will cause the Brownian motion inside the solution to intensify and the capture stability to decrease. Thermophoretic optical tweezers use the photothermal effect to generate a thermal field distribution. The combined effect of the thermal gradient and the Soret coefficient of the sample converts the photothermal effect into a major boost for sample capture, generating a stronger capture force than the pure light field. Therefore, generating a thermal field is also very important.

[0003] In the existing technology, a thin gold nanofilm is generally plated on the glass surface to form a thermal field. However, its absorption rate drops sharply when the wavelength is greater than 500nm, and the absorption rate in the infrared band is less than 0.04. This means that the light source band of the thermophoretic optical tweezers based on the gold film is greatly limited, resulting in the intensity distribution of the thermal field is not strong enough, making it difficult to achieve high-precision control of multiple targets over a large range.

[0004] Therefore, how to adjust and optimize the above-mentioned membrane structure so that it has a larger and more stable thermal gradient field and complete efficient thermophoretic optical tweezers capture of samples under different laser wavelengths is one of the technical problems that need to be urgently solved in this field. Summary of the invention

[0005] In view of this, the present invention provides a composite membrane structure for thermophoretic optical tweezers capture, which has a larger gradient and a more stable thermal gradient field, and can achieve efficient thermophoretic optical tweezers capture of samples under different laser wavelengths.

[0006] The invention also provides a method for preparing the composite membrane structure.

[0007] In a first aspect, the present invention provides a composite membrane structure for thermophoretic optical tweezers capture, wherein the composite membrane structure comprises, from bottom to top, a substrate, a chromium membrane layer, and a silicon dioxide membrane layer.

[0008] In an optional implementation, the chromium film layer has a thickness of 10 nm-15 nm.

[0009] In an optional embodiment, the thickness of the silicon dioxide film layer is 25nm-30nm.

[0010] In an alternative embodiment, the substrate comprises a glass slide.

[0011] In a second aspect, the present invention further provides a method for preparing the above-mentioned composite membrane structure, comprising the following steps: (1) Plating a film on the substrate surface to deposit a chromium film layer; (2) Depositing a silicon dioxide film layer on the chromium film layer by radio frequency magnetron sputtering.

[0012] In an optional embodiment, the primary coating method includes at least one of evaporation and secondary radio frequency magnetron sputtering.

[0013] In an optional embodiment, the evaporation step is performed under vacuum, and the vacuum degree is ≤10 -1 Pa.

[0014] In an optional embodiment, the current of the evaporation step is 25A-30A.

[0015] In an optional embodiment, the power of the secondary RF magnetron sputtering is 120W-130W.

[0016] In an optional embodiment, the power of the radio frequency magnetron sputtering is 115W-120W.

[0017] In an optional embodiment, before the substrate is evaporated, a cleaning and drying step is also included.

[0018] In an optional embodiment, a secondary cleaning step is also included before the secondary RF magnetron sputtering step.

[0019] In an optional embodiment, the drying method is drying with an inert gas.

[0020] In an optional embodiment, the secondary cleaning method is plasma cleaning.

[0021] In a third aspect, the present invention also provides an application of the above-mentioned composite membrane structure in thermophoretic optical tweezers capture.

[0022] In a fourth aspect, the present invention further provides an optical tweezers device, comprising the above-mentioned composite membrane structure.

[0023] Compared with the prior art, the technical solution of the present invention has the following advantages: 1. The composite membrane structure provided by the present invention for thermophoretic optical tweezers capture comprises, from bottom to top, a substrate, a chromium film layer and a silicon dioxide film layer. The present invention relies on laser irradiation of the composite membrane structure to generate a local non-uniform temperature field, and utilizes the thermal gradient field near the hot spot to achieve thermophoretic capture of particles; specifically: the chromium film material is a material with extremely strong thermal effect, and its absorption rate is above 0.3 in the ultraviolet to near-infrared band, which is higher than the gold material of traditional thermophoretic optical tweezers; at the same time, compared with the thermal conductivity of the gold film, the thermal conductivity of the chromium film is about half of that of the gold film, which means that the thermal diffusion of the chromium film is slower, and a stronger thermal gradient can be formed locally. Under the condition of the same thickness (10nm), chromium is more efficient than gold, graphene and other commonly used photothermal materials. The hot spot temperature gradient field generated by the focused light field is more powerful, and the photothermal capture of particles can be completed in a longer wavelength band; but since hexavalent chromium is toxic to biological cells, if the heat loss on the material surface is allowed, the present invention magnetically plates a silicon dioxide film layer on the surface of the chromium film, which can effectively isolate the direct contact between the sample and the chromium film, prevent the sample from sticking to the chromium film, and complete the thermophoretic optical tweezers capture and manipulation of the sample while ensuring that the sample is not affected by the toxicity of the chromium film; at the same time, silicon dioxide is stable in nature, and its chemical structure is similar to that of a glass slide, and will not produce excessive deformation and qualitative changes due to the existence of thermal effects.

[0024] When photothermal capture is performed on a chromium-silicon dioxide substrate, an array light trap (such as 100 or more) generated by a spatial light modulator can be used to capture particles on-chip at the array photothermal traps, and the capture power at each point is less than 0.1 mW. Under the same laser power, it can produce a larger and more stable thermal gradient field than substrate materials such as gold and graphene to assist in more types of photothermal capture.

[0025] 2. The composite membrane structure provided by the present invention for thermophoretic optical tweezers capture limits the thickness of the chromium film layer to 10nm-15nm. If the chromium film layer is too thin, the thermal effect of the chromium film is too weak and the film cannot be formed, which affects the subsequent magnetron sputtering effect of silicon dioxide. If it is too thick, the light transmittance is poor.

[0026] 3. The composite membrane structure for thermophoretic optical tweezers capture provided by the present invention limits the thickness of the silicon dioxide film layer to 25nm-30nm. If the silicon dioxide film layer is too thin, it will not form a film, and if it is too thick, the thermal effect of the chromium film layer will be weakened.

[0027] 4. The method for preparing the composite film structure for thermophoretic optical tweezers capture provided by the present invention limits the current of the evaporation step to 25A-30A, so that the thickness of the chromium film layer is more uniform and accurate.

[0028] 5. The preparation method of the composite membrane structure for thermophoretic optical tweezers capture provided by the present invention, the one-time coating method is preferably RF magnetron sputtering, and the silicon dioxide film layer can be laid after the chromium film is plated by RF magnetron sputtering. RF magnetron sputtering is Ar ion bombardment of the target material, and the target material is sputtered out with higher energy, which can adhere more firmly, and the purity and uniformity of the film layer will be better, and the sample contamination can be reduced.

[0029] 6. The method for preparing the composite membrane structure for thermophoretic optical tweezers capture provided by the present invention limits the secondary cleaning method to plasma cleaning, which ensures the cleanliness of the substrate and improves the hydrophilicity, making it easier to adhere to the silicon dioxide film layer. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0031] Figure 1 This is a thermophoresis capture effect diagram of the composite membrane structure prepared in Example 1 of the present invention at 0s; Figure 2 This is a 10s thermophoresis capture effect diagram of the composite membrane structure prepared in Example 1 of the present invention; Figure 3 This is a graph showing the thermophoresis capture effect of the composite membrane structure prepared in Example 1 of the present invention in 5 minutes; Figure 4 This is a thermophoresis capture effect diagram of the composite membrane structure prepared in Example 1 of the present invention in 10 minutes; Figure 5 This is a thermophoresis capture effect diagram of the composite membrane structure prepared in Example 2 of the present invention at 0s; Figure 6 This is a 10s thermophoresis capture effect diagram of the composite membrane structure prepared in Example 2 of the present invention; Figure 7 This is a thermophoresis capture effect diagram of the composite membrane structure prepared in Example 2 of the present invention in 5 minutes; Figure 8 This is a thermophoresis capture effect diagram of the composite membrane structure prepared in Example 2 of the present invention in 10 minutes; Fig. 9 is a comparison diagram of thermal gradients of the composite membrane structures prepared in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention; Fig.10 It is a comparison chart of light absorption rate curves of the chromium film layer prepared in Example 1 of the present invention and the gold film layer prepared in Comparative Example 1 at different wavelengths. DETAILED DESCRIPTION

[0032] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0033] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0034] In the existing technology, chromium is often used as an adhesive for glass substrates and gold, and the excellent photothermal effect of chromium film is rarely used for thermophoretic optical tweezers capture. The main reason is that hexavalent chromium is toxic to the captured sample; at the same time, chromium film has excellent hydrophilicity, and the particles are easily adhered to the substrate.

[0035] In order to solve the problems existing in the above-mentioned related technologies, according to the first aspect of the present invention, the present invention provides a composite membrane structure for thermophoretic optical tweezers capture, wherein the composite membrane structure comprises, from bottom to top, a substrate, a chromium film layer and a silicon dioxide film layer; the thickness of the chromium film layer is 10nm-15nm; the thickness of the silicon dioxide film layer is 25nm-30nm; the substrate can be other materials that adhere to chromium, including a glass slide.

[0036] The present invention provides a composite membrane structure for thermophoretic optical tweezers, and the composite membrane structure includes a substrate, a chromium film layer and a silicon dioxide film layer from bottom to top. The present invention relies on laser irradiation of the composite membrane structure to generate a local non-uniform temperature field, and uses the thermal gradient field near the hot spot to achieve thermophoretic capture of particles; specifically: the chromium film material is a material with extremely strong thermal effect, and its absorption rate is above 0.4 in the ultraviolet to near-infrared band, which is higher than the gold material of traditional thermophoretic optical tweezers; at the same time, compared with the thermal conductivity of the gold film, the thermal conductivity of the chromium film is about half of that of the gold film, which means that the thermal diffusion of the chromium film is slower, and a stronger thermal gradient can be formed locally. Under the condition of the same thickness (10nm), chromium is more efficient than gold, graphene and other commonly used photothermal materials. The hot spot temperature gradient field generated by the focused light field is more powerful, and the photothermal capture of particles can be completed in a longer wavelength band; but since hexavalent chromium is toxic to biological cells, if the heat loss on the material surface is allowed, the present invention magnetically plates a silicon dioxide film layer on the surface of the chromium film, which can effectively isolate the direct contact between the sample and the chromium film, prevent the sample from sticking to the chromium film, and complete the thermophoretic optical tweezers capture and manipulation of the sample while ensuring that the sample is not affected by the toxicity of the chromium film; at the same time, silicon dioxide is stable in nature, and its chemical structure is similar to that of a glass slide, and will not produce excessive deformation and qualitative changes due to the existence of thermal effects.

[0037] When photothermal capture is performed on a chromium-silicon dioxide substrate, an array light trap (e.g., 100 or more) generated by a spatial light modulator can be used to capture particles on-chip at the array photothermal traps with a capture power of less than 0.1 mW at each point. Under the same laser power, it can produce a larger and more stable thermal gradient field than substrate materials such as gold and graphene to assist in more types of photothermal capture.

[0038] The thickness of the chromium film layer is limited to 10nm-15nm. If the chromium film layer is too thin, the thermal effect of the chromium film is too weak and a film cannot be formed, which affects the subsequent RF magnetron sputtering effect of silicon dioxide. If it is too thick, the light transmittance is poor. The thickness of the silicon dioxide film layer is limited to 25nm-30nm. If the silicon dioxide film layer is too thin, a film cannot be formed. If it is too thick, the thermal effect of the chromium film layer will be weakened.

[0039] In a second aspect, the present invention further provides a method for preparing the above-mentioned composite membrane structure, comprising the following steps: (1) After cleaning the substrate once, the substrate is allowed to stand, dried with an inert gas (preferably nitrogen), and then subjected to a coating process to deposit a chromium film layer; the coating process includes at least one of evaporation and secondary radio frequency magnetron sputtering; the evaporation process is performed under vacuum, and the vacuum degree is ≤10 -1 Pa, the current is 25A-30A; or, the power of the secondary RF magnetron sputtering is 120W-130W; the primary cleaning method can be adjusted according to the different substrates; (2) After the chromium film layer is laid, the substrate is subjected to a secondary cleaning step, and then a silicon dioxide film layer is laid by a radio frequency magnetron sputtering. The power of the radio frequency magnetron sputtering is 115W-120W. The secondary cleaning method is plasma cleaning. The plasma is air, etc.

[0040] In the present invention, the current of the evaporation step is limited to 25A-30A, so that the thickness of the chromium film layer is more uniform and accurate, and the chromium film layer has an appropriate thickness.

[0041] In the present invention, the secondary cleaning method is limited to plasma cleaning to ensure the cleanliness of the substrate and improve the hydrophilicity, making it easier to adhere to the silicon dioxide film layer.

[0042] In a third aspect, the present invention also provides an application of the above-mentioned composite membrane structure in thermophoretic optical tweezers capture.

[0043] In a fourth aspect, the present invention further provides an optical tweezers device, comprising the above-mentioned composite membrane structure.

[0044] The power of RF magnetron sputtering is determined by the type of target material, the distance between the target and the substrate, the type and pressure of the working gas, the deposition rate, and the geometric structure of the coating chamber. The magnetron sputtering machine used in the present invention is model SP-LC6-A06, and the manufacturer is Silicon Technology Co., Ltd.

[0045] The composite membrane structure prepared by the present invention can realize the photothermal electric capture and photothermal diffusion phoresis capture of cell biological samples and plastic particles with a Soret coefficient less than 0; by adding surfactants (tri(hexadecyl)methylammonium chloride, polyethylene glycol, etc.) to the sample, the photothermal electric capture and photothermal diffusion phoresis capture of cell biological samples and plastic particles with a Soret coefficient greater than 0 can also be realized.

[0046] The present invention is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed by the present invention.

[0047] Example 1 This embodiment provides a method for preparing a composite membrane structure for capture by thermophoretic optical tweezers, comprising the following steps: (1) Use acetone solution to preliminarily clean the glass slide substrate for 15 minutes to wash away impurities on the substrate surface, recover the acetone solution, and then clean it with ethanol solution for 15 minutes to further ensure the cleanliness of the substrate and wash away excess residual acetone solution. After cleaning, let it stand for 5 minutes and blow it dry with nitrogen; (2) Fix the clean glass slide on the sample stage of the coating machine, place a chrome strip between the electrodes of the coating machine, and evacuate the vacuum to 10 -1 Pa below, a 10nm chromium film layer was obtained by evaporation at a current of 30A; (3) The substrate after the chromium film is evaporated is plasma cleaned, and then a 25 mm silicon dioxide layer is laid by radio frequency magnetron sputtering at a power of 115 W to obtain a composite film structure.

[0048] Example 2 This embodiment provides a method for preparing a composite membrane structure for capture by thermophoretic optical tweezers, comprising the following steps: (1) Use acetone solution to preliminarily clean the glass slide substrate for 15 minutes to wash away impurities on the substrate surface, recover the acetone solution, and then clean it with ethanol solution for 15 minutes to further ensure the cleanliness of the substrate and wash away excess residual acetone solution. After cleaning, let it stand for 5 minutes and blow it dry with nitrogen; (2) Fix the clean glass slide on the sample stage of the coating machine, place a chrome strip between the electrodes of the coating machine, and evacuate the vacuum to 10 -1 Pa below, a 15nm chromium film layer was laid by radio frequency magnetron sputtering at a power of 120W; (3) After the chromium film layer is evaporated, the substrate is plasma cleaned once, and then a 28 mm silicon dioxide layer is laid by radio frequency magnetron sputtering at a power of 117 W to obtain a composite film structure.

[0049] Example 3 This embodiment provides a method for preparing a composite membrane structure for capture by thermophoretic optical tweezers, comprising the following steps: (1) Use acetone solution to preliminarily clean the glass slide substrate for 15 minutes to wash away impurities on the substrate surface, recover the acetone solution, and then clean it with ethanol solution for 15 minutes to further ensure the cleanliness of the substrate and wash away excess residual acetone solution. After cleaning, let it stand for 5 minutes and blow it dry with nitrogen; (2) Fix the clean glass slide on the sample stage of the coating machine, place a chrome strip between the electrodes of the coating machine, and evacuate the vacuum to 10 -1 Pa below, a 12nm chromium film layer was obtained by evaporation at a current of 25A; (3) The substrate after the chromium film is evaporated is plasma cleaned, and then a 30 mm silicon dioxide layer is laid by radio frequency magnetron sputtering at a power of 120 W to obtain a composite film structure.

[0050] Comparative Example 1 This comparative example provides a method for preparing a composite membrane structure for photothermophoresis capture, which is basically the same as the steps of Example 1, except that the chromium film layer is replaced by a gold film layer of the same thickness.

[0051] Comparative Example 2 This comparative example provides a method for preparing a composite membrane structure for photothermophoresis capture, which is basically the same as the steps of Example 1, except that the chromium membrane layer is replaced by a graphene layer of the same thickness.

[0052] Experimental Example 1 The composite membrane structures prepared in the above-mentioned Examples 1 and 2 are subjected to efficient thermophoretic optical tweezers capture at a laser wavelength of 532 nm. The specific steps are as follows: the composite membrane structures prepared in the above-mentioned Examples are fixed on a microscope stage respectively, and light beams of different laser wavelengths are modulated into a 10×10 array spot using an SLM (liquid crystal spatial light modulator). The particles can be captured on-chip at the photothermal trap, and the capture power of each point is less than 0.1 mW, and it is ensured that it is focused on the substrate (the laser energy is focused on the substrate with a 20x objective lens with an NA of 0.45). A thermophilic cell yeast sample (Soret coefficient <0) is added to complete a high-throughput thermophoretic optical tweezers capture, and irradiated under a laser with a wavelength of 532 nm. The thermophoretic capture effect diagram is shown in FIG. 1 for 0s, 10s, 5min, and 10min. Figure 1-Figure 8 As shown in the figure, it can be seen that after the laser is turned on for 0s, the cell samples are distributed randomly and are not in the photothermal trap ( Figure 1 and Figure 5 ), the distribution of particles in space when the laser is turned on for 10 seconds. Some cell samples have been stably captured in the hot trap, and the rest are also approaching the hot trap ( Figure 2 and Figure 6 ); When the laser is turned on for 5 minutes, most of the cell samples have been stably captured in the hot trap ( Figure 3 and Figure 7 ); 10 minutes after the laser was turned on, most of the cell particles had been stably captured in the heat trap ( Figure 4 and Figure 8 ), the photothermal trap capture efficiency is above 85%, indicating that the composite membrane structure prepared by the present invention can realize the thermophoresis optical tweezers capture of cells, and the capture stability is good.

[0053] Experimental Example 2 The composite membrane structure prepared in the above-mentioned Example 1 and Comparative Examples 1-2 was captured by efficient thermophoretic optical tweezers at a laser wavelength of 532nm. The specific steps are as follows: using the finite element simulation method, the same laser wavelength and laser power (2W) were incident on the surface of the composite membrane material prepared in Example 1 and Comparative Examples 1-2, and the thermal gradient map at the two-dimensional section line from -1 micron to 1 micron on the XY plane was calculated and drawn. The results are shown in Fig. 9 As shown in the figure, it can be seen that under the same laser power and laser wavelength conditions, the absolute value of the temperature gradient of the composite film structure prepared in Example 1 at the hot spot (x-coordinate is 0nm) is the largest, which is about 3-4 times that of the composite film structure prepared in Comparative Example 1 at the same thickness, and far exceeds the composite film structure in Comparative Example 2. The larger the temperature gradient, the greater the photothermal force, and the better the capture effect. Therefore, the composite film structure prepared by the present invention can achieve more stable capture and manipulation, and can achieve larger flux thermal capture of particles under limited laser energy. The range of the thermal gradient field is related to factors such as the substrate material. The range of the thermal gradient field in this experimental example is -1000nm to 1000nm.

[0054] Experimental Example 3 The chromium film layer and the gold film layer prepared in the above-mentioned embodiment 1 and comparative example 1 are subjected to efficient thermophoretic optical tweezers capture at different laser wavelengths. The specific steps are: physical simulation is performed using the light absorption rate parameters of the chromium film layer and the gold film layer, and the light absorption rate diagrams of the chromium film layer and the gold film layer at different wavelengths are calculated and plotted, see Fig.10 As shown in the figure, it can be seen that the light absorption rate of the gold film layer prepared in Comparative Example 1 is greatly reduced in the band of >500nm, while the chromium film layer structure prepared in Example 1 can still maintain good light absorption ability in the band of 250nm-1750nm, and because the thermal conductivity of the chromium film layer is smaller than that of the gold film layer in Comparative Example 1, a larger temperature gradient field is generated under the same conditions, and the photothermal capture of particles can be completed in a longer band.

[0055] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A composite membrane structure for thermophoretic optical tweezers capture, characterized in that: The composite film structure comprises, from bottom to top, a substrate, a chromium film layer and a silicon dioxide film layer.

2. The composite membrane structure according to claim 1, characterized in that: The thickness of the chromium film layer is 10nm-15nm.

3. The composite membrane structure according to claim 1, characterized in that: The thickness of the silicon dioxide film layer is 25nm-30nm.

4. The composite membrane structure according to claim 1, characterized in that: The substrate includes a glass slide.

5. A method for preparing a composite membrane structure according to any one of claims 1 to 4, characterized in that: The steps include: (1) Plating the substrate once to deposit a chromium film layer; (2) Depositing a silicon dioxide film layer on the chromium film layer by radio frequency magnetron sputtering.

6. The preparation method according to claim 5, characterized in that: The primary coating method includes at least one of evaporation and secondary radio frequency magnetron sputtering; The evaporation step is carried out under vacuum, and the vacuum degree is ≤10 -1 Pa; The current of the evaporation step is 25A-30A; The power of the secondary radio frequency magnetron sputtering is 120W-130W.

7. The preparation method according to claim 5, characterized in that: The power of the radio frequency magnetron sputtering is 115W-120W.

8. The preparation method according to claim 6, characterized in that: Before the substrate is evaporated, a cleaning and drying step is also included; Before the secondary RF magnetron sputtering step, a secondary cleaning step is also included; The drying method is to use inert gas to dry; The secondary cleaning method is plasma cleaning.

9. Use of the composite membrane structure according to any one of claims 1 to 4 or the composite membrane structure prepared by the preparation method according to any one of claims 5 to 8 in thermophoretic optical tweezers capture.

10. An optical tweezers device, characterized in that: The invention comprises the composite membrane structure described in any one of claims 1 to 4 or the composite membrane structure prepared by the preparation method described in any one of claims 5 to 8.

Citation Information

Patent Citations

  • Method for preparing inorganic tin-based perovskite solar cell by physical vapor deposition

    CN107742661A

  • Wood extraction solution for the detoxification of hexavalent chromium contained in waste liquids and wastewater, and its manufacturing method

    JP3820484B1

  • Novel Lactobacillus plantarum KNUT 0118 strain and uses thereof

    KR102293724B1

  • Methods and systems for assembly of particle superstructures

    US20180236486A1

  • Methods and systems for optothermal particle control

    US20190113453A1